UPAYA MENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PENERAPAN METODE GASING DALAM PERKALIAN DUA DIGIT PADA SISWA KELAS V SDN BILAPORAH 1 - Dwi Puspitasari, Cahyani; Adis Syauqi Nayif, Mohamad; Arini Hidayati, Putri; Eka Nur Anggraeni, Shelvi; Amalia Nur Azizah, Natasya; Setyawan, Agung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the application of the GASING method (easy, fun, and fun) in mathematics learning as well as to improve learning outcomes, accuracy, and students' ability to understand and solve story problems in the two-digit multiplication material of grade V students of SDN Bilaporah 1. This research is motivated by the low mathematical understanding of students, especially in multiplication calculation operations, which is characterized by a lack of mastery of basic concepts, low accuracy in arithmetic, and difficulties in understanding story problems. This study uses a quantitative approach with a type of pre-experimental research (pre-experimental design) through a one-group pretest-posttest design. The research was carried out at SDN Bilaporah 1 with 20 research subjects in class V. Data sources were obtained from test results, questionnaires, interviews, and documentation. Data collection techniques include giving pretests and posttests, distributing questionnaires, and interviews with classroom teachers. The research instrument is in the form of written tests and questionnaires that have gone through validity tests and reliability estimates with the help of SPSS Statistic 23 software. The data analysis technique used descriptive and inferential statistics, with prerequisite tests in the form of normality tests and hypothesis testing using t-tests. The results of the study show that the application of the GASING method is able to improve students' mathematics learning outcomes, which is characterized by an increase in average scores and the number of people who achieve learning completion. In addition, the GASING method also increases students' accuracy in the calculation process and their ability to understand and solve story problems. Thus, it can be concluded that the GASING method is effective in improving the mathematical understanding of elementary school students. Based on the results of the research, it is recommended that teachers apply the GASING method in a sustainable manner in mathematics learning and develop more innovative learning variations to improve the quality of learning.